THE EXEMPLARY VALUES OF ACHMAD ABDRAHIM WAHAB - Abdul Rahmat Jailani Tonggadu; Helman Manay; Andris K. Malae (Satmata: Journal of Historical Education Studies, 2025)
This study aims to analyze the exemplary values embedded in the life journey of Achmad Abdrahim Wahab as a local figure in Gorontalo, particularly in terms of simplicity, honesty, and generosity, as well as to examine their relevance to character education and local history learning. This research employs a qualitative method with a historical approach. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions using a descriptive-analytical method. The results indicate that Achmad Abdrahim Wahab is a role model who consistently practiced a simple lifestyle despite coming from a well-established family, upheld honesty in carrying out his duties as a government official, and demonstrated generosity through tangible contributions to the field of education, such as providing land and financial support for the establishment of secondary schools and higher education institutions in Gorontalo. These values not only reflect personal integrity but also have significant implications for shaping the character of the younger generation and strengthening local historical identity. This study recommends the utilization of local historical figures’ life stories as contextual learning resources in character education and history teaching in schools.